2016
DOI: 10.1109/taffc.2015.2435780
|View full text |Cite
|
Sign up to set email alerts
|

Two Techniques for Assessing Virtual Agent Personality

Abstract: Abstract-Personality can be assessed with standardized inventory questions with scaled responses such as "How extraverted is this character?" or with open-ended questions assessing first impressions, such as "What personality does this character convey?" Little is known about how the two methods compare to each other, and even less is known about their use in the personality assessment of virtual agents. We tested what personality virtual agents conveyed through gesture alone when the agents were programmed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 58 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Human's personality can be generally expressed through verbal and non-verbal communication channels. With respect to the non-verbal social cues, personality indicators have been described in [11,30,[34][35][36]39,49]. Bevaqua et al [11] used facial expressions and gestures to model a virtual agent with features based on psychological principles.…”
Section: Verbal and Non-verbal Cues In Modelling Robot's Personalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Human's personality can be generally expressed through verbal and non-verbal communication channels. With respect to the non-verbal social cues, personality indicators have been described in [11,30,[34][35][36]39,49]. Bevaqua et al [11] used facial expressions and gestures to model a virtual agent with features based on psychological principles.…”
Section: Verbal and Non-verbal Cues In Modelling Robot's Personalitymentioning
confidence: 99%
“…Results showed that the same gesture type can convey different meanings depending on its quality and thus on how it was interpreted. Liu et al [30] aimed to assess whether an agent could convey through gestures a personality trait such as extroversion and introversion. In their experiments, participants were asked to evaluate an agent's personality while watching video clips of it portraying the characteristics of extroversion or introversion.…”
Section: Verbal and Non-verbal Cues In Modelling Robot's Personalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have employed user studies to evaluate the effectiveness of digital character animation (Kokkinara and McDonnell 2015;McDonnell 2012;Liu et al 2016), as well as to study the impact of variety (McDonnell et al 2008;O'Sullivan 2009).…”
Section: Facial Animationmentioning
confidence: 99%
“…Therefore, a specialized voice activation technology and the inhabitants’ preferred keywords are applied to allow inhabitants to more naturally customize their speech communications with their devices. Specifically, personalized language models that recognize the customized device names are suggested, since it is important to accurately recognize the device name when each end user issues a personalized command for a device [ 32 ].…”
Section: Proposed Conceptmentioning
confidence: 99%